Thermal time in sprinkler-irrigated lowland rice - Bartz, Alex Cristiano; Muttoni, Martina; Alberto, Cleber Maus; Streck, Nereu Augusto; Machado, Géter Alves; Giacomeli, Robson; Helgueira, Diogo Balbé; Moura, Diogo da Silva (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate methods of thermal time calculation and the duration of the development stages of lowland rice (Oryza sativa) irrigated by sprinkling. The experiment was conducted during three growing seasons (2010/2011, 2011/2012, and 2014/2015), with five irrigation water depths, six cultivars, and four replicates. Six methods of thermal time calculation were tested: two using the minimum basal temperature; two using the minimum and optimum temperatures; and two using the minimum, optimum, and maximum basal temperatures. For the thermal time calculation, the crop development cycle was divided into the vegetative, reproductive, and grain-filling phases. The methods that used the three cardinal temperatures showed the lowest coefficients of variation for most of the developmental phases. Both irrigation water depths and rice cultivars affected the thermal time of the development stages. The greater the water availability, the lower the duration of the development cycle. Thermal time values depend on the calculation method.